The Availability of ISO 9001-2015 requirements - Moyassar I. Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research attempt to study ISO 9001-2015 requirements availability in CIHAN University campus, the research problem interpreting by the main question deals with the requirements of ISO 9001-2015 which are represented by ten clauses, three of them are key clauses (scope, normative references, terms and definitions). The research use a questionnaire as a main tool for gathering data, a sample of nine department's heads asked about the availability of seven clauses (context of the organization, leadership, planning, support, operation, performance evaluation and improvement), according to three options (applied and documented, applied and not documented, not applied and not documented). The result show that the highest percentage coverage gained by second clause (5. Leadership), and the lower percentage were for third one (6. Planning), while the application and documentation of clauses 1, 8 (context of the organization) and (operation) gained the upper rate of agreements between the department's heads ((77%) for both). The researcher suggests to overlaps difficulties and fills the gaps to make all clauses available, so it's necessary to make some preparations dealings with deploying the philosophy of ISO, so the nine departments’ heads invited to put their concerns at planning activities by define actions and external environment.